2005
DOI: 10.1002/rcm.2169
|View full text |Cite
|
Sign up to set email alerts
|

A simple method of isolation of chloramphenicol in honey and its estimation by liquid chromatography coupled to electrospray ionization tandem mass spectrometry

Abstract: To detect sub-ppb levels of the antibiotic chloramphenicol in honey matrix, a convenient method of extraction and measurement using liquid chromatography with detection by tandem mass spectrometry (LC/MS/MS) was developed. Honey samples fortified with chloramphenicol and isotopically labeled chloramphenicol were extracted using diatomaceous-based supported liquid-liquid extraction cartridges to generate a standard calibration curve. Four MS/MS transitions were used for quantification and four other transitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Several reports have described estimation of CAP by liquid chromatography-tandem mass spectrometry (LC/MS/MS) in shrimp (Neuhaus et al, 2002;Rønning et al, 2006), meat (Bogusz et al, 2004;Cooper et al, 1998;Li et al, 2002;Mottier et al, 2003;Rønning et al, 2006), milk (Guy et al, 2004;Huang et al, 2006;Rønning et al, 2006), and honey (Ashwin et al, 2005;Forti et al, 2005;Huang et al, 2006;Ortelli et al, 2004;Rønning et al, 2006;Turnipseed et al, 2002;Vanhoenacker et al, 2003;Verzegnassi et al, 2003;Vivekanandan et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Several reports have described estimation of CAP by liquid chromatography-tandem mass spectrometry (LC/MS/MS) in shrimp (Neuhaus et al, 2002;Rønning et al, 2006), meat (Bogusz et al, 2004;Cooper et al, 1998;Li et al, 2002;Mottier et al, 2003;Rønning et al, 2006), milk (Guy et al, 2004;Huang et al, 2006;Rønning et al, 2006), and honey (Ashwin et al, 2005;Forti et al, 2005;Huang et al, 2006;Ortelli et al, 2004;Rønning et al, 2006;Turnipseed et al, 2002;Vanhoenacker et al, 2003;Verzegnassi et al, 2003;Vivekanandan et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Some methods describe direct extraction and clean-up of chloramphenicol from honey with C 18 SPE (Bogusz et al, 2004) or use of C 18 SPE for further clean-up of an ethyl acetate extract (Ortelli et al, 2004) or of a dichloromethane/acetone extract (Forti et al, 2005) of the honey samples. Other methods involve use of supported liquid-liquid extraction (LLE) on diatomaceous earth cartridges (Kaufmann and Butcher, 2005;Vivekanandan et al, 2005), MIP (Shi et al, 2010) and IAC (Mackie et al, 2013) techniques.…”
Section: Confirmatory Methodsmentioning
confidence: 99%
“…Three samples contained more than 2 µg/kg and six samples contained between 0.3 and 1.7 µg/kg (Vivekanandan et al, 2005 In Romania, 12 honey samples (year of collection not reported) collected from beekeepers in Romania were analysed by LC-MS (LOD/LOQ = 0.13/0.27 µg/kg) and chloramphenicol was detected in one sample (1.4 µg/kg) (Mǎrghitaş et al, 2010). In addition, Simion et al (2011) analysed 82 honey samples, collected from beekeepers, using ELISA (LOD/LOQ/CCα/CCβ not reported).…”
Section: Occurrence In Food Of Animal Originmentioning
confidence: 99%
“…Chloramphenicol (CAP) is a broad spectrum antibiotic derived from the soil bacterium Streptomyces, ubiquitously used for treating bacterial diseases in veterinary and aquaculture practice [1]. However, it has the potential to cause serious toxic effects on humans and animals when given by mouth or injection, with non-target effects such as bone marrow depression, aplastic anemia, hypoplastic anemia, thrombocytopenia, as well as granulocytopenia [2].…”
Section: Introductionmentioning
confidence: 99%